2017
DOI: 10.1002/2017gb005630
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of ENSO on air‐sea oxygen exchange: Observations and mechanisms

Abstract: Models and observations of atmospheric potential oxygen (APO ≃ O2 + 1.1 * CO2) are used to investigate the influence of El Niño–Southern Oscillation (ENSO) on air‐sea O2 exchange. An atmospheric transport inversion of APO data from the Scripps flask network shows significant interannual variability in tropical APO fluxes that is positively correlated with the Niño3.4 index, indicating anomalous ocean outgassing of APO during El Niño. Hindcast simulations of the Community Earth System Model (CESM) and the Insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 145 publications
(171 reference statements)
0
35
1
Order By: Relevance
“…. More complex coupling is also possible on interannual time-scales 29 , such as the weaker lagged air-sea CO 2 flux compared to O 2 during El Nino events 30 . www.nature.com/scientificreports www.nature.com/scientificreports/ Atmospheric O 2 and CO 2 measurements have previously been applied to estimate global land and ocean CO 2 sinks, but relied on ocean heat content estimates and model-based oceanic O 2 -to-heat ratios to correct for climate-driven O 2 outgassing [31][32][33] .…”
mentioning
confidence: 99%
“…. More complex coupling is also possible on interannual time-scales 29 , such as the weaker lagged air-sea CO 2 flux compared to O 2 during El Nino events 30 . www.nature.com/scientificreports www.nature.com/scientificreports/ Atmospheric O 2 and CO 2 measurements have previously been applied to estimate global land and ocean CO 2 sinks, but relied on ocean heat content estimates and model-based oceanic O 2 -to-heat ratios to correct for climate-driven O 2 outgassing [31][32][33] .…”
mentioning
confidence: 99%
“…More recently, the long O 2 and CO 2 data set of Tohjima et al [2015] over the western Pacific Ocean showed that the amplitude of the western Pacific equatorial APO bulge in this region was anticorrelated to El Niño-Southern Oscillation (ENSO), with a suppressed APO bulge over the western Pacific during El Niño conditions, which is mostly attributed to changes in atmospheric circulation associated with meridional shifts in the ITCZ (Intertropical Convergence Zone). The results of Tohjima et al [2015] are contradictory to those of a previous modeling study by Rödenbeck et al [2008], who found a significant positive correlation between APO anomalies over the tropical Pacific Ocean and ENSO variability; however, this discrepancy has recently been reconciled by Eddebbar et al [2017], who showed that the response of APO to ENSO variability differs significantly between the western and central/eastern Pacific. Model simulations suggest that an APO bulge of comparable shape and magnitude should exist over the Atlantic ], but these predictions have never been verified with observational data until now.…”
Section: Introductioncontrasting
confidence: 56%
“…They also found, however, that up to~25% of the equatorial annual mean APO interannual variability might be caused by changes in equatorial APO outgassing fluxes in the western Pacific, which are also associated with the ENSO cycle. The modeling study by Rödenbeck et al [2008] also found a significant correlation between ENSO variability and APO anomalies, albeit in the opposite direction to that found by Tohjima et al [2015], and more recently, Eddebbar et al [2017] showed that the response of APO to ENSO variability differs between the western and central/eastern Pacific and confirmed that the suppression of the APO bulge over the western Pacific is mainly dominated by the weakening of trade winds.…”
Section: Discussionmentioning
confidence: 62%
“…Conducting atmospheric inversion analyses based on the APO data from the Scripps observation network, Rödenbeck et al (2008) suggested anomalous outgassing of APO from the equatorial region during El Niño periods, while Tohjima et al (2015) found a suppressed equatorial peak during El Niño periods based on the western Pacific observations. Eddebbar et al (2017) reconciled these conflicting results by predicting the existence of a zonal dipole-like El Niño-Southern Oscillation (ENSO) response in the equatorial Pacific based on several ocean process-based models and an atmospheric transport model. These results suggest that enhanced zonal coverage of the atmospheric observations in the equatorial Pacific is needed to constrain the full basin-scale ENSO response.…”
Section: Evaluation Of Outgassing Effect (Z Eff )mentioning
confidence: 96%